Perancangan dan Penataan Kawasan di Sepanjang Sungai Banjir Kanal Timur Kelurahan Bugangan dan Kelurahan Rejosari dengan Konsep Livable Riverfront Settlement Kecamatan Semarang TImur, Kota Semarang - R.D.A. Puteri; R.S. Pulungan; H.D. Tambunan; H.M. Rahmi; R. Amalia; A.R. Davinaldo; M.W. Hidayat; M. Mazz; D.D. Febriani; Z. Zulhamdi; H. Sima (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Livable Riverfront Settlement is a concept design that is mindful of environmental livability housing which is in the nearby river. The concept of Liveable Riverfront Settlement is a derivative of the concept of macro-regions planning Sustainable Riverfront Settlement and the concept of the planning area of meso Ecological Riverfront Settlement. The purpose of this writing is focused on the design of landing neighborhood along the Eastern Canal flood in Bugangan and Rejosari village who have a problem like slums and squatters settlement, the occurrence of floods, the lack of open space, the low quality of the environment and housing backlog.In this article using quantitative methods with descriptive analysis techniques, and the qualitative method with interviews and observations of the field. The results of the identification and analysis of the design of landing (UDGL) settlement along the Eastern Canal flood in Bugangan and Rejosari village based on 3 indicators, the improvement of the economy through the provision of employment (job creation), the management of flood risks through the improvement of environmental quality (disaster risk management), as well as the provision of housing that is affordable and livable (livable housing provision).